A Tale of Winglets: Evolution of Flight Morphology in Stick Insects - Zeng Y.; O'Malley C.; Singhal S.; Park S.; Chen X.; Dudley R.; Faszly Rahim (Frontiers Media S.A., 2024)
Indexed by WOS/SCOPUS/ERA